2011
DOI: 10.1111/j.1365-2796.2011.02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum homocysteine, holotranscobalamin, folate and cognition in the elderly: a longitudinal study

Abstract: Objectives. To examine the associations between serum homocysteine (tHcy), holotranscobalamin (holoTC, the biologically active fraction of vitamin B12) and folate and cognitive functioning in a longitudinal population-based study of Finnish elderly subjects.Subjects and design. tHcy, holoTC and folate were measured at baseline in 274 dementia-free subjects aged 65-79 years from the Cardiovascular Risk Factors, Aging and Dementia study. Subjects were re-examined 7 years later, and global cognition, episodic mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 35 publications
5
66
1
8
Order By: Relevance
“…Indeed, a review by Smith (41) some years ago reported that 90 out of 100 published cross-sectional and prospective studies showed a link between elevated homocysteine and/or low B-vitamins concentrations with cognitive dysfunction. Most of these studies have focused on elevated plasma homocysteine concentrations (42)(43)(44)(45)(46) , and/or a combination of suboptimal status of folate and vitamin B 12 (47)(48)(49)(50)(51)(52)(53)(54) and to a much lesser extent on vitamin B 6 ( 55,56) . To the authors' knowledge, no published study thus far has focused on riboflavin alone as a potential contributor to cognitive health.…”
Section: Evidence Linking B-vitamins With Brain Health In Ageingmentioning
confidence: 99%
“…Indeed, a review by Smith (41) some years ago reported that 90 out of 100 published cross-sectional and prospective studies showed a link between elevated homocysteine and/or low B-vitamins concentrations with cognitive dysfunction. Most of these studies have focused on elevated plasma homocysteine concentrations (42)(43)(44)(45)(46) , and/or a combination of suboptimal status of folate and vitamin B 12 (47)(48)(49)(50)(51)(52)(53)(54) and to a much lesser extent on vitamin B 6 ( 55,56) . To the authors' knowledge, no published study thus far has focused on riboflavin alone as a potential contributor to cognitive health.…”
Section: Evidence Linking B-vitamins With Brain Health In Ageingmentioning
confidence: 99%
“…In addition to its close association to the etiology of pernicious anemia [105] and subacute combined degeneration [106], vitamin B 12 deficiency is related, through homocysteine, with dissimilar diseases such as Alzheimer's disease [107,108], dementia [109,110], depression [111], stroke [112,113], pulmonary embolism [114,115], acute myocardial infarction, and coronary heart disease [116].…”
Section: Vitamin B 12 Deficiencymentioning
confidence: 99%
“…Большинство исследований демонстрируют корре-ляцию между низкой концентрацией фолиевой кис-лоты и высоким уровнем гомоцистеина с умственной неполноценностью, высоким риском развития демен-ции и болезни Альцгеймера [12,22].…”
Section: статистические данныеunclassified